SAFETY ASSESSMENTS FOR SUPPORTING THE APPLICATION OF NUCLEAR TECHNOLOGY IN INDONESIA AND A COMPREHENSIVE STUDY ON HIGH NATURAL RADIOACTIVITY AREA - Abarrul Ikram; Ismanto Jumadi; Nurokhim Nurokhim; Eka Djatnika Nugraha (BATAN, 2020)
SAFETY ASSESSMENTS FOR SUPPORTING THE APPLICATION OF NUCLEAR TECHNOLOGY IN INDONESIA AND A COMPREHENSIVE STUDY ON HIGH NATURAL RADIOACTIVITY AREA. Historically BATAN was established to investigate the negative impacts of nuclear explosions previously conducted in the Pacific area. However, this governmental institute is presently tasked to carry out research and development as well as services in the field of radiation safety and metrology. Therefore, this study aim to determine the activities carried out by BATAN in assessing the safety of workers and the environment. For instance, a standard source of dosimetry laboratory (SSDL) is used in calibration services to successfully support radiotherapy, with the highest achievement in the Designated Institute (DI) for Ionizing Radiation. The health research covers the application of gamma rays to create malaria vaccine, diagnose metabolic diseases with nuclear medicine techniques, and microdosimetry through radiodiagnostic assessment. This study also determined the effective dose and epidemiological study of radioecology and radiation biology in Mamuju (HBRA), which provides a unique opportunity to examine the health effects of chronic low-level radiation exposure to humans. Furthermore, the authors collaborated with Hirosaki University to obtain valuable information on the essential need to assess the health and physical status as well as cytogenetic and deoxynucleotide acid (DNA) damages in the lymphocytes of local populations. Dosimetry study was conducted by direct measurement in the field area by analyzing external radiation exposure of indoor and outdoor gamma dose rate. The internal radiation assessment was conducted by taking urine and inhaled air (radon) from the residents. Studies through the cytogenetic response supported by γ-H2AX, G0, and G2 micronucleus assays and TP53 showed no impacts on the natural radiation with significant differences compared to the control. Marine radioecology studies and radionuclides monitoring throughout the Indonesian archipelago showed no negative impacts as well. Nuclear emergency practice needs to be routinely conducted in the Center for strengthening safety and security cultures.